2015
DOI: 10.21608/asnj.2015.182467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polyethylene Eye Covers Dressing On Preventing Corneal Complications On Critically Ill Patients At Assiut University Hospital

Abstract: Prevention of corneal complications for intensive care unit patients is effective way to avoid corneal damage. Polyethylene covering is transparent dressing creates moist chamber providing a barrier against tear-film evaporation and providing physical barrier to organisms Aim: this study was carried out to investigate the impact of polyethylene eye covers dressing on preventing corneal complications. Design: A quasi-experimental design. Setting: Trauma Intensive Care Unit at Assiut University Hospital. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The findings from this study confirmed the effectiveness of polyethylene covers compared to eye drops in preventing ocular surface diseases [ 6 , 17 , 18 , 34 ]. However, this finding was contrary to the results reported by Nikseresht (2019) [ 28 ] possibility due to the differences in the age and physical conditions of patients, their length of hospital stay, the dose of anesthetics received, and the type of patients admitted to the intensive care unit.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The findings from this study confirmed the effectiveness of polyethylene covers compared to eye drops in preventing ocular surface diseases [ 6 , 17 , 18 , 34 ]. However, this finding was contrary to the results reported by Nikseresht (2019) [ 28 ] possibility due to the differences in the age and physical conditions of patients, their length of hospital stay, the dose of anesthetics received, and the type of patients admitted to the intensive care unit.…”
Section: Discussionsupporting
confidence: 76%
“…A polyethylene cover is approximately 0.01 mm thick, easily adheres to surfaces [ 12 , 16 ], protects the eyes by creating a moist chamber, prevents the evaporation of tears, keeps the eye surface naturally moist, and prevents microorganisms from entering the eye, especially during suctioning and feeding through a nasogastric tube (NGT) [ 8 ]. These easy-to-use covers prevent possible corneal complications and keep the eyes clean and closed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients on mechanical ventilation who use sedatives or neuromuscular blocking drugs are more likely to have a corneal problem due to weakened defenses. The research results of Hearne,3 Kuruvilla,33 and Atia34 supported the association between the length of mechanical ventilation and the emergence of eye problems. The association between sedative use and a higher risk of ocular surface conditions.…”
Section: Discussionmentioning
confidence: 62%
“…This agrees with Atiaa et al, who studied the impact of polyethylene eye covers dressing on preventing corneal complications on critically ill patients and documented that polyethylene eye cover created a moist chamber and provided a barrier against tear-film evaporation. 34 Many studies 8,11,14,18,19 have documented that PCs were more effective in reducing the incidence of corneal complications in intensive care patients in comparison with other methods, and PC and simple eye ointment are recommended as effective EC methods in ICU. This is reinforced by the findings of Alansari et al,…”
Section: Assessment Of Eyelid Closurementioning
confidence: 99%